Molecular characterization of chloramphenicol-resistant Haemophilus parainfluenzae and Haemophilus ducreyi. - Roberts, M C (1985)
We examined chloramphenicol-resistant Haemophilus parainfluenzae and Haemophilus ducreyi strains isolated in various parts of the world. The antibiotic resistance determinants were located on conjugative plasmids in H. ducreyi, but were chromosomally located in H. parainfluenzae. Both species produced chloramphenicol acetyltransferases (CATs) that were sensitive to 5,5'-dithiobis(2-nitrobenzoic acid) like the enteric type II and Haemophilus influenzae CAT enzymes, but differed from these enzymes in elution patterns and subunit molecular weight. Southern blot analysis showed the H. parainfluenzae and H. ducreyi CAT genes were molecularly related to the enteric type II class as well as the H. influenzae CAT. Heterogeneity of the physiochemical properties of the CATs was observed; however, the data suggested that all three Haemophilus spp. have a common ancestral source for the CATs.